UF/IFAS Strawberries beyond the USA: A Success Story from Egypt: HS1411, 5/2021 - EL-Borai, Fahiem; Whitaker, Vance M. (EDIS, 2021)
Currently, Florida strawberry varieties are grown in over 70 countries spread across six continents. The main objective of this Extension publication is to communicate the benefits of licensing UF/IFAS strawberries outside of the USA, with a special focus on Egypt. The target audience of this new 6-page publication of the UF/IFAS Horticultural Sciences Department includes those involved in the strawberry industry as well as the general public. Written by Fahiem EL-Borai and Vance M. Whitaker. https://edis.ifas.ufl.edu/hs1411